Auswirkungen von Rauchen spezifiziert nach Zigaretten pro Tag und maternalem Body-Mass-Index auf hypertensive Schwangerschaftserkrankungen - Voigt, M.; Neudecker, K.; Schneider, K.T. M.; Olbertz, D.; Briese, V.; Straube, W.; Straube, S. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
We have previously described the prevalence in pregnancy of hypertension, proteinuria, oedema and preeclampsia/eclampsia according to maternal body mass index (BMI) and smoking status. We found that these disorders were less frequent among smoking women. To investigate whether this relationship is causal or a chance finding, we here present an analysis according to BMI and smoking specified according to the number of cigarettes consumed per day.Data were from the German Perinatal Survey of 1998–2000. We classified women by BMI as underweight (BMI<18.5 kg/m2), normal weight (BMI 18.5–24.99 kg/m2), overweight (25.0–29.99 kg/m2), or obese (BMI≥30 kg/m2). Smoking was categorised as being a non-smoker or smoking 1–7, 8–14 or ≥ 15 cigarettes per day. Datasets from 433 669 singleton pregnancies with information on maternal BMI and smoking were included in the analysis.In all BMI categories hypertension, moderate to severe oedema, and preeclampsia/eclampsia became less prevalent with increasing maternal cigarette consumption. Dose-dependence was not convincing for proteinuria.Dose-dependence in the relationship between smoking and hypertensive disorders of pregnancy argues against a chance finding and for a causal relationship.
Keywords: smoking; hypertensive disorders; pregnancy